The Comparative Law on the Distribution of Power in the 1945 Constitution of the Republic of Indonesia and the Constitution of the Republic Timor Leste - I Nyoman Prabu Buana Rumiartha; Ni Luh Gede Astariyani; Armindo Moniz Amaral (Fakultas Hukum Universitas Mataram, 2022)
The research purposes is to explain the comparison of the legal division of powers in the constitution in the 1945 Constitution of the Republic of Indonesia and in the Constitution of the Republic Democratic Timor Leste. The division of powers within a country, both in Indonesia and in Timor Leste, are stipulates in a constitution, in this case a state that protects and guarantees the implementation of human rights and other civil rights and limits its powers in a balanced manner between the interests of state administrators and their citizens. The research method used in this study was normative legal research. In addition, this research also applied comparative legal research method is a research methodology carried out by comparing one legal system to another, an activity in which experts compare the positive legal system of a nation to that of other nations. In this case, legal comparison of Indonesia and Timor Leste. The novelty of this research is to examine and analyze comparative law on the distribution of power in the constitutions of Indonesia and Timor Leste, it can be explained that there is a difference in the division of power. In Indonesia there is constitutive power, executive power, legislative power, judicial power, examining/inspective power, and monetary power, while in Timor Leste it is based on the constitution of the Democratic Republic of Timor Leste division of power consisting of the power of the president, the power of the national parliament, the power of the government and the power of the court.